On Synchronous Supereruptions - Cisneros de León, Alejandro; Mittal, Tushar; de Silva, Shanaka L.; Self, Stephen; Schmitt, Axel K.; Kutterolf, Steffen (Frontiers in Earth Science, 2022)
The Youngest Toba Tuff (YTT) supereruption from Toba Caldera in Sumatra at ca. 74,000 yr BP is the largest volcanic event recorded in the Pleistocene. Intriguingly, recent radioisotopic dating of the near antipodal Los Chocoyos (LCY) supereruption from the Atitlán caldera in Guatemala finds an identical age within uncertainties to that of YTT. This opens the question of whether these near-synchronous supereruptions may be a coincidence or could be a consequence of each other? Using the known eruptive record from the past 2 Myr, we find that the likelihood of having two near antipodal supereruptions (>1,000 km3 tephra volume) within centuries (<400 yr), as suggested by volcanic proxies and annual counting layer chronology in the ice core records, is very small (0.086%), requiring a non-random cause and effect. Considering this analysis, we speculate that one potential physical mechanism that could explain the temporal relationship between these supereruptions is that seismic energy released during YTT eruption focused on the antipodal region, where concentrated stresses ultimately promoted the eruption of the perched LCY magma system (or vice versa). This supereruption “double-whammy” may thus be the more compelling source of the significant environmental impacts often attributed individually to the YTT supereruption. Improving the existing age information of YTT and LCY, and a better understanding of caldera collapse events will enable further testing of the hypothesis that synchronous supereruptions did not result by pure chance.